Circular Economy in the Household Sector in Jakarta - Pravitasari, Endyastuti; Abriandi, Abriandi; Nabila, Alfina; Anggoro, Hendi Tri; Felicia, Nita; Slamet, Yogi (Penerbit Goodwood, 2025)
Purpose: The primary objective of this research is to investigate the factors and explore the potential of collaboration among stakeholders that influence the successful implementation of a circular business model for household waste management.Research: A qualitative approach employed to gather the data using In-depth interviews which are semi-structured interviews will be conducted with seven key stakeholders representing industry, community, government, and society. Open-ended exploratory questions will be used to delve into their experiences, perceptions, and insights regarding circular business models, observation, and literature review to identify existing knowledge, theories, and empirical evidence.Results: The findings of this research are to identify the essential elements of a successful circular business model, determine the factors that positively or negatively impact the implementation of circular business models, and identify potential areas for collaboration among stakeholders.Conclusions: To develop an effective and sustainable circular business model for waste management in the household sector we need Business Model Innovation. The factors that influence the success of circular business model implementation in the household sector that are most mentioned in the results of this study are as follows. Cooperation between various related parties to support the development and implementation of circular business model.Limitations: The interview sample size of seven participants may limit the generalizability of the findings. A larger sample size could provide a more comprehensive understanding of the diverse perspectives and experiences of stakeholders.Contribution: This research will contribute to the existing body of knowledge on circular economy and household waste management in Jakarta. The findings will be valuable for policymakers, businesses, and communities to develop and implement effective strategies for sustainable waste management.